2016
DOI: 10.3847/1538-4357/833/1/109
|View full text |Cite
|
Sign up to set email alerts
|

The Preferential Tidal Stripping of Dark Matter Versus Stars in Galaxies

Abstract: Using high resolution hydrodynamical cosmological simulations, we conduct a comprehensive study of how tidal stripping removes dark matter and stars from galaxies. We find that dark matter is always stripped far more significantly than the stars -galaxies that lose ∼80% of their dark matter, typically lose only 10% of their stars. This is because the dark matter halo is initially much more extended than the stars. As such, we find the stellar-to-halo size-ratio (measured using r eff /r vir ) is a key parameter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
119
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(133 citation statements)
references
References 67 publications
14
119
0
Order By: Relevance
“…The figure shows that galaxies that have lost < 90% of the maximum dark matter mass still retain > 90% of their maximum stellar mass. These results are broadly consistent with work by Smith et al (2016) who showed that galaxies around clusters that lose ∼ 80% of their dark matter mass only lose ∼ 10% of their stellar mass. Our results are not directly comparable since we do not follow the galaxies' particles from peak to z = 0 in the same way as Smith et al (2016).…”
Section: Radial Trajectoriessupporting
confidence: 92%
See 1 more Smart Citation
“…The figure shows that galaxies that have lost < 90% of the maximum dark matter mass still retain > 90% of their maximum stellar mass. These results are broadly consistent with work by Smith et al (2016) who showed that galaxies around clusters that lose ∼ 80% of their dark matter mass only lose ∼ 10% of their stellar mass. Our results are not directly comparable since we do not follow the galaxies' particles from peak to z = 0 in the same way as Smith et al (2016).…”
Section: Radial Trajectoriessupporting
confidence: 92%
“…Previous studies have suggested a strong correlation between the stellar mass and peak mass of galaxies (e.g. Peñarrubia et al 2008;Smith et al 2016). As we have found in this study, most of the single and grouped galaxies reach their peak total mass around the time they first became part of Figure 14.…”
Section: S7 S8mentioning
confidence: 98%
“…Therefore we cannot directly measure the effect that tidal stripping might have on their baryonic component, which of course is the only component directly visible to us. However, as shown by Smith et al (2016), the relationship between dark matter tidal stripping and stellar tidal stripping in hydrodynamical cosmological simulations is actually quite well constrained: only halos that have lost more than ∼80% of their dark matter halo are likely to suffer any stellar stripping. Then, as the remaining ∼ 20% of the dark matter is stripped, the stellar fraction reduces rapidly towards 0%.…”
Section: Discussionmentioning
confidence: 99%
“…In Smith et al (2016), the authors study the stripping of stellar and dark matter in galaxies during their infall into simulated clusters, and found that 18% of the galaxies were undergoing important star formation during accretion, with an increase in stellar mass higher than 15%. We test the influence of strongly star forming galaxies by removing all galaxies that increase their stellar mass by more that 50% during their infall, which represent 10% of the total number of satellite galaxies in our sample.…”
Section: Evolution Of Mass Vs R Satmentioning
confidence: 99%
“…Conversely, subhaloes will be subject to destructive influence from their host, and their dark matter will be gradually stripped by tidal forces. This effect has been highlighted in a number of analyses of N-body simulations for host haloes ranging from the size of the Milky Way (Hayashi et al 2003a;Kravtsov et al 2004;Diemand et al 2007;Buck et al 2019) to that of the most massive galaxy clusters (Ghigna et al 1998;Gao et al 2004;Tormen et al 2004;van den Bosch et al 2005;Giocoli et al 2008;Xie & Gao 2015;Smith et al 2016;Rhee et al 2017), where subhalo mass loss is well described by analytical models of tidal stripping (Mamon 2000;Gan et al 2010;Han et al 2016;Hiroshima et al 2018).…”
mentioning
confidence: 99%